Identification of a novel cosavirus species in faeces of children and its relationship with acute gastroenteritis in China. (August 2017) - Yu, J.-M.; Ao, Y.-Y.; Li, L.-L.; Duan, Z.-J.
Abstract: Objectives: To assess the prevalence of human cosavirus (HCosV) in China and to determine the association of a novel HCosV (Cosa-CHN) with acute gastroenteritis (AGE). Methods: A case–control study with 461 paired stool samples from diarrhoea and healthy children was conducted. Real-time PCR and nested PCR were used to detect the HCosVs. Rapid amplification of cDNA ends was used to obtain the ends of the Cosa-CHN. Results: Known HCosVs were detected in two control samples, while Cosa-CHN was detected in eight (1.7%) and six (1.3%) of the case and control samples respectively. The complete genome of Cosa-CHN comprises 7213 bp. The P1 and P2 regions of the Cosa-CHN were closely related to those of HCosV B, while the P3 region was most similar to that of HCosV D, albeit with low amino acid identities (66 and 67% respectively). Phylogenetic analyses of the polyprotein and partial VP3/VP1 regions indicated that Cosa-CHN could be classified as a novel species (tentatively named HCosV G) in cosavirus. There was no significant difference in detection rate (p 0.59) or mean virus load (p 0.43) of Cosa-CHN between the cases and controls. Statistical analysis revealed no association between Cosa-CHN and AGE (p 0.76), and the virus did not exacerbate clinical symptoms. Conclusions: A low prevalence of HCosV was detected, but a novel Cosavirus species was found in children with and without gastroenteritis in this study. The evidence did not support a causative role for the novel virus in paediatric AGE.